Effect of Heat Treatment on Tensile Strength of Al7075/Al2O3/SiCp Hybrid Composite by Stir Casting Technique. (2018) - Ravi Kumar, M.; Reddappa, H.N.; Suresh, R.; Gangadharappa, M.
Abstract: The main Purpose of this investigation is to study the effect of heat treatmenton Al 7075 reinforced by silicon carbide (SiC) and Alumina (Al2 O3 ) Metal Matrix Composites (MMCs). Composites of varying SiC content (3, 6 and 9 wt. %) and Al2 O3 content (2, 4 and 6 wt. %) were produced by stir casting technique. Microstructural observation exposed non-homogeneous distribution of reinforcement particles in the Al matrix. The result shows that increasing in wt. % of reinforcements in Al 7075 matrix increased in tensile strength and heat treatment process is also dramatically impact on the tensile properties of composites